2020
DOI: 10.3389/fmars.2020.00683
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Macroalgal Surface Metabolites on the Settlement of the Benthic Dinoflagellate Ostreopsis cf. ovata

Abstract: Macroalgae constitute one of the preferred substrates of the benthic dinoflagellate Ostreopsis cf. ovata. Across the Mediterranean Sea, this toxic microalga has been shown to thrive on the surface of various species of macroalgae, including Chlorophyta, Rhodophyta, and Phaeophyceae. Interestingly, some Dictyotaceae are characterized by a low abundance of cells of O. cf. ovata on their surface. Based on the antifouling properties of some specialized metabolites produced by seaweeds, macroalgal metabolites have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
(139 reference statements)
1
7
0
4
Order By: Relevance
“…Taken together, these results may strengthen the hypothesis of a light-dependent DMSP biosynthesis, especially in the case of lowtemperature conditions (Karsten et al, 1992). Moreover, DMSP is also produced by many microalgae, including dinoflagellates and diatoms (Bullock et al, 2017), and the potential origin of DMSP at the surface of T. atomaria could also be linked to such epiphytes that were identified on several Dictyotaceae including T. atomaria (Ternon et al, 2020). Besides, DMSP constitutes a source of carbon and sulfur for a large diversity of bacteria, especially those from the Roseobacter clade (Howard et al, 2008;Curson et al, 2011;Dogs et al, 2017).…”
Section: Short-term Responses Of Algal Surface Microbiota and Metabolomesupporting
confidence: 71%
See 1 more Smart Citation
“…Taken together, these results may strengthen the hypothesis of a light-dependent DMSP biosynthesis, especially in the case of lowtemperature conditions (Karsten et al, 1992). Moreover, DMSP is also produced by many microalgae, including dinoflagellates and diatoms (Bullock et al, 2017), and the potential origin of DMSP at the surface of T. atomaria could also be linked to such epiphytes that were identified on several Dictyotaceae including T. atomaria (Ternon et al, 2020). Besides, DMSP constitutes a source of carbon and sulfur for a large diversity of bacteria, especially those from the Roseobacter clade (Howard et al, 2008;Curson et al, 2011;Dogs et al, 2017).…”
Section: Short-term Responses Of Algal Surface Microbiota and Metabolomesupporting
confidence: 71%
“…atomaria could also be linked to such epiphytes that were identified on several Dictyotaceae including T . atomaria (Ternon et al ., 2020). Besides, DMSP constitutes a source of carbon and sulfur for a large diversity of bacteria, especially those from the Roseobacter clade (Howard et al ., 2008; Curson et al ., 2011; Dogs et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the substrate preferences of Ostreopsis spp. are still ambiguous (Vila et al, 2001;Cohu et al, 2013;Sparrow et al, 2017;Ternon et al, 2020;Tester et al, 2020), although some studies reported larger abundances on some substrates compared to others (Vila et al, 2001(Vila et al, , 2012Mohammad-Noor et al, 2007;Widiarti, 2008;Cabrini et al, 2010;Totti et al, 2010;Accoroni et al, 2011Accoroni et al, , 2012Accoroni and Totti, 2016;Yong et al, 2018;Boisnoir et al, 2019;Bravo et al, 2020;Lee et al, 2020). Such comparisons are tricky because of the limits of cell quantification in function of the type of substrate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(Aligizaki and Nikolaidis, 2006;Monti et al, 2007;Okolodkov et al, 2007;Totti et al, 2010 ;Ismael and Halim, 2012), Dictyota spp. (Cohu et al, 2013 ;Blanfune et al, 2015;González et al, 2019;Gémin et al, 2020 ;Ternon et al, 2020), and Cystoseira sensu lato spp. (Aligizaki and Nikolaidis, 2006;Monti et al, 2007;Aligizaki and Nikolaidis, 2008;Blanfune et al, 2015;Catania, 2017;Moncer et al, 2017;Meroni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation